LEGAL REVIEW OF THE POSITION OF THE REGULATION OF THE HEAD OF THE CAPITAL CITY AUTHORITY OF NUSANTARA AS LOCAL LEGAL PRODUCT: TINJAUAN YURIDIS TERHADAP KEDUDUKAN PERATURAN KEPALA OTORITA IBU KOTA NUSANTARA SEBAGAI PRODUK HUKUM DAERAH - Ahmad Reihan Thoriq; Mohammad Akmal Taris Hakim (Journal Social Sciences and Humanioran Review, 2024)
The relocation of the National Capital from Jakarta to Kalimantan has sparked various public discussions, particularly concerning the constitutionality of the Nusantara Capital City Authority (IKN) system, where the term "authority" is not explicitly mentioned in the 1945 Constitution. Furthermore, provisions in the IKN Law stating that the Head of the IKN Authority is equivalent to a minister have also raised ambiguity regarding the position of the Head of the IKN Authority and the status of the legal regulations issued. This study aims to address these issues. The research methodology employed is normative juridical with a legislative approach. The findings indicate that the IKN system and the position of the Head of the IKN Authority align with Article 18B paragraph (1) of the 1945 Constitution, which recognizes the specificity of regions. The Head of the IKN Authority is appointed directly by the President after consultation with the DPR, in accordance with the constitution, which does not require direct election by the people. Regulations issued by the Head of the IKN Authority retain the status of local regulations, without requiring approval from the Regional Representative Council (DPRD).